Microrobots for the Healthcare System from Design to Application-State of the Art and Challenges - Moshayedi, Ata Jahangir; Khan, Amir Sohail; Davari, Mehdi; Mokhtari, Tahmineh; Emadi Andani, Mehran (EAI Endorsed Transactions on AI and Robotics, 2024)
Micro robots, miniature robotic devices typically ranging from micrometers to a few millimeters in size, hold immense potential in various fields, particularly healthcare. Their diminutive stature enables access to intricate anatomical regions previously unreachable, facilitating targeted drug delivery, localized treatment, and precise monitoring. These robots offer numerous advantages, including enhanced maneuverability, reduced invasiveness, and minimized tissue damage. By navigating through complex biological environments, micro robots can deliver therapies with unprecedented precision, improving treatment efficacy and patient outcomes. Additionally, their small size allows for minimally invasive procedures, reducing recovery times and enhancing patient comfort. Overall, micro robots represent a groundbreaking technological advancement with the potential to revolutionize healthcare delivery and significantly benefit human well-being.Their small size enables access to intricate anatomical regions for targeted drug delivery, localized treatment, and precise monitoring. Despite challenges like size constraints and navigation complexities, innovative solutions and interdisciplinary collaboration are driving their advancement in improving healthcare outcomes.
Keywords: Micro robot; Service robot; Design; sensors; Navigation